The promotion and development of small and medium enterprises : an investigation of the effectiveness of assistance programmes and the participation of SMEs in the export sector in Swaziland : a thesis submitted in fulfilment of the requirements for the degree of Doctor pf Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Magagula, Phumzile Lomagugu (Massey University, 2002)
Small and Medium Enterprises (SMEs) are increasingly occupying a prominent position in the policy agendas of both developed and developing countries, owing to the recognition of the significant potential contribution that these enterprises can make to national economic and social development. In addition, the exporting successes of SMEs in industrialised countries, in the last decade, have highlighted the critical role of SMEs in export- and private-sector-led economic growth, consequently many developing countries are refocusing their attention on the search for strategies and the design of policies and assistance programmes aimed at the promotion and development of their SME sectors. Sound policies to assist more SMEs to export, however, must be informed by a clear understanding of any systematic differences between current exporters and non-exporters. This study employed a multi-method approach, making use of both qualitative and quantitative methods, to investigate the nature and extent of SMEs' export involvement and the effectiveness of SME promotion and development programmes in Swaziland. In particular various firm-specific and managerial characteristics believed to shape the export behaviour of SMEs were utilised to investigate why some SMEs are exporters and some are not. The results of this study revealed that for many SMEs in Swaziland the export orientation is zero. The few that are exporting are mostly found in the manufacturing, agriculture and forestry industries. Foreign language proficiency and the frequency of business-related foreign trips are amongst the significant variables in explaining export propensity amongst SMEs in Swaziland. On the effectiveness of assistance programmes, this investigation showed that awareness levels and usage rates differ among assistance programmes and by the firms' market orientation. Generally, managers of SMEs are more aware of (and have accessed more) domestically oriented programmes than export oriented ones, which to some extent explains SMEs' poor export involvement. A policy recommendation that arises instinctively from this study is that official support, financial or otherwise, is likely to bear more fruit in exporting if targeted towards currently non-exporting SMEs and aimed at upgrading the language skills of managers, and assisting with bona fide business-related functions outside the country.
Keywords: Small business exports; Economic development, Swaziland; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management